Patterns in the Timing of Corporate Event Waves - Rau, P. Raghavendra; Stouraitis, Aris (Journal of Financial and Quantitative Analysis, 2011)
Abstract Corporate events happen in waves. In this paper, we examine the timing patterns of 5 different types of corporate event waves (new stock and seasoned equity issues, stock- and cash-financed acquisitions, and stock repurchases) using a comprehensive data set of more than 151,000 corporate transactions over the 25-year period from 1980 to 2004. We document a distinctive pattern, previously not found in the literature, in the way stock-related waves form. Corporate waves seem to start with new issue waves (seasoned equity offering preceding initial public offering waves), followed by stock-financed merger waves, followed in turn by repurchase waves. Our results hold over separate decades and across industries. Our results seem consistent with both the neoclassical efficiency hypothesis and the misvaluation hypothesis, and there are distinct periods when one or the other appears dominant.